Studi In Silico: Senyawa Aktif Akar Senggugu (Clerodendrum serratum) terhadap Penghambatan Reseptor Human Chitotriosidase-1 (hCHIT1) sebagai Antiasma - Herdini Herdini (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
ABSTRACT Asthma is a chronic inflammatory disease that is usually characterized by airway inflammation. One of the plants that has been used for a long time to treat asthma is the root of Clerodendrum serratum. This study aimed to determine the potential of the active compound of senggugu root as an anti-asthma which was carried out in silico including prediction of molecular docking, physicochemical properties, and prediction of toxicity. Molecular docking prediction uses PLANTS, while physicochemical properties and toxicity uses the ProTox and pkCSM websites. Molecular docking results showed that the compounds apigenin-7-glucoside, β-Dihydrofucosterol, icosahydropicenic acid, D-mannitol, and queretaroic acid had better affinity than theophylline as the reference compound. Based on lipinski's role of five analysis, from the seven active compounds, there is apigenin-7-glucoside was not meet the requirements for lipinski's role of five but can still qualify for use as new drug compounds by increasing their permeability. The compound β-Dihydrofucosterol is the best candidate, because β-Dihydrofucosterol shows good parameters of absorption, distribution, metabolism and excretion. For prediction of β-Dihydrofucosterol toxicity is in class IV which is still safer than the comparator drug theophylline. The β-Dihydrofucosterol compound is also predicted not to have mutagenic, hepatotoxic, or sensitive effects for the skin. Keywords: asthma, Clerodendrum serratum, in silico, molecular docking